Metabolic fingerprinting of three Malaysian ginger (Zingiber officinale Roscoe) using gas chromatography-mass spectromertry - Mahdi, Harith Jameel; Budi Muljono, Retno Andayani; -, Ishak (Science Publications, 2010)
Problem statement: There is a chemical variation among different ginger cultivars detected by previous studies including the volatile and non-volatile oleo-resins. In this study we try to determine whether these variations are related to a generic factor rather than environmental or intrinsic factors. Approach: A comprehensive metabolic fingerprinting from the leaves of three micro-propagated ginger cultivars Bukit Tinggi, Tanjung Sepat and Sabah was performed using a Gas Chromatography-Mass Spectrometry (GC-MS). Constituents of the ginger leaves were first extracted and then fractionated into methanolic and chloroform. The samples were subsequently methoximated and silylated prior to GC-MS analysis. Results: By applying this technique, we detected more than 300 compounds (polar and non-polar) in total originated from each ginger cultivars. Based on the GC-MS fragmentation, three different classes of metabolites were detected from the ginger cultivars, namely amino acids, carbohydrates and organic acids. A qualitative variation on the type of ginger metabolites was observed, albeit no marked different found in the level of the metabolites. Conclusion: Apparently the chemical variations among the three ginger cultivars were due to genetic effects since almost all other environmental and intrinsic factors were eliminated.